2019
DOI: 10.1101/580563
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Metabolic activity affects response of single cells to a nutrient switch in structured populations

Abstract: Microbes live in ever-changing environments where they need to adapt their metabolism to different nutrient conditions. Many studies have characterized the response of genetically identical cells to nutrient switches in homogenous cultures, however in nature microbes often live in spatially structured groups such as biofilms where cells can create metabolic gradients by consuming and releasing nutrients. Consequently, cells experience different local microenvironments and vary in their phenotype. How does this… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 48 publications
1
19
0
Order By: Relevance
“…In contrast to advection dominated planktonic life style, bacterial cells in diffusion dominated systems often self-engineer their immediate surroundings (a process frequently termed niche construction 20 ). For example, single species biofilms engage in cross-feeding interactions through divergent behavior of spatially segregated subpopulations experiencing fundamentally different growth conditions 21,22 . Overall, trophic interactions have the potential to shape the emerging community patterns during bacterial range expansion.…”
mentioning
confidence: 99%
“…In contrast to advection dominated planktonic life style, bacterial cells in diffusion dominated systems often self-engineer their immediate surroundings (a process frequently termed niche construction 20 ). For example, single species biofilms engage in cross-feeding interactions through divergent behavior of spatially segregated subpopulations experiencing fundamentally different growth conditions 21,22 . Overall, trophic interactions have the potential to shape the emerging community patterns during bacterial range expansion.…”
mentioning
confidence: 99%
“…While there are many more examples of the use of X-ray CT for assessing soil structure [31] , [29] , [13] , [52] , [19] , the applications to structured environments go beyond soils. Bradley et al [6] used X-ray nanotomography – X-ray CT at sub-micron resolution – with Zernike phase-contrast (to enhance the subject/background contrast) for examining the distribution and depth of human fibroblast cells grown on polymer scaffolding.…”
Section: Recent Methods For Investigating Microbial (Micro)environmenmentioning
confidence: 99%
“…Microfluidics has been used to establish biofilms and monitor growth and inherent metabolic dynamics under controlled conditions. In a recent study, E. coli monolayers were cultured in a device designed to establish a glucose gradient in a series of dead-end chambers containing the bacteria (measuring 40 µm × 60 µm) after introducing flow perpendicular to the chamber opening [13] . Fluorescence analysis of gene reporter expression indicated that cells at the front of the chamber metabolised glucose and secreted acetate whereas cells towards the back of the chamber (which were glucose limited) could metabolise the secreted acetate.…”
Section: Recent Methods For Investigating Microbial (Micro)environmenmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, generating or altering community structure through sIgA‐mediated clumping may influence cross‐feeding and therefore growth rates in both targeted and untargeted species, as has been observed in biofilms . Finally, highly cooperative species may actually grow faster when kin‐association is enforced by enchained growth.…”
Section: Determinants and Consequences Of Clumpingmentioning
confidence: 99%